Nutrient Stocks, Nutrient Cycling, and Soil Changes in Cocoa Ecosystems: A Review - Hartemink, Alfred E. (Advances in Agronomy, 2005)
It is generally assumed that agricultural systems with perennial crops are more sustainable than systems with annual crops. Soil erosion is negligible and perennial crops have more closed nutrient cycling. Moreover, inorganic fertilizers are used more commonly in cash crops such as perennial crops so that soil fertility decline and nutrient mining are less likely to occur. In the past decades, considerable research has been devoted to the quantification of nutrient stocks and nutrient cycling in agro-ecosystems. This article reviews the main stocks and flows of nutrients in cocoa ecosystems for several cocoa-growing regions in the tropics. Most of the nitrogen is found in the topsoils, and less than 10% of the total N stock is in the cocoa and shade trees. Nitrogen in the annual litter fall is about 20 to 45% of the total N in the vegetation and 2 to 3% of the total N in the soil. The accumulation of potassium is low in cocoa ecosystems, and in most systems the total amount in the biomass is equivalent to the available P content in the topsoil. Phosphorus in the annual litter fall is about 10 to 30% of the total P in the vegetation and 10 to 40% of the available P in the soil. Potassium is a major nutrient in mature cocoa. Stocks of exchangeable K in the topsoil vary from 100 to 550 kg ha−1, and high K levels in the soil correspond to high K levels in the vegetation and litter. Partial nutrient balances were calculated that compares the losses, addition, and transfer of N, P, and K. The nutrient balance is negative in the absence of inorganic fertilizers, especially for K. Rainwash and litter fall are key components in the cycling of nutrients of cocoa ecosystems. The amount of nutrients transferred by rainwash is less than 8 kg ha−1 for N and P but varies from 38 to more than 100 kg ha−1 year−1 for K. Most soils under cocoa had a lower fertility when compared to primary forest, although soil chemical properties seem to settle at equilibrium levels. This review shows that large amounts of nutrients in cocoa ecosystems are transferred each year and that such nutrient cycling is essential for maintaining cocoa production.